Determinación de hdl y ldl en sangre de las mujeres adultas de la asociación de comerciantes minoristas Manuel Arévalo (Acomimar) de la III etapa de la Urb. Manuel Arévalo del distrito de La Esperanza – Trujillo (enero 2007) - Guevara Salazar, Mónica de Lourdes (2008)
Authors: Monica Lourdes Salazar Guevara and Flor de Maria Guillén Ortiz, thesis Type I: "Determination of HDL and LDL in the blood of Adult Women of the Association of Retail Merchants Manuel Arevalo of the Third Stage of Manuel Arevalo District of La Esperanza - Trujillo (January 2007) ", Advisers: Dra. Q.F. Miriam Gutierrez Ramos. MsC. Q.F. Salomon Alva Bazan, 30 pages, 2008, Faculty of Pharmacy and Biochemistry, National University of Trujillo. It made the following problem: What are the levels of HDL and LDL in the blood of adult women of the Association of Retail Merchants Manuel Arevalo from the third stage of Manuel Arevalo District La Esperanza-Trujillo. (January 2007)? The material consists of the study of 120 adult women patients working in the market called: Association of Retail Merchants Manuel Arevalo District of La Esperanza - Trujillo. Respective samples were taken and were subjected to analysis by the method specified, thereby determining the values of HDLc and LDLc of each patient. The goal was to determine the concentration of HDL and LDL, and to educate each patient outcome in question, and then guide them and point out the guidelines to follow are needed to preserve their health.